Spice Production, Marketing, and Value Chain in Ethiopia - Abdurahman Wondimnew (The Scientific World Journal)
The purpose of this paper was to document and organize spice production, marketing, and value chain in Ethiopia. Spice is the most essential farming product. Several native and exotic spices are grown by smallholder farmers across the country because Ethiopia has diverse agroecology and favorable climate conditions. The spice subsector has great potential for the country’s economic development and poverty alleviation, cultivation, preparation, transport, and merchandising of spices and herbs. Spice market indicates the commodity value of spices. The major problems regarding the marketing system of spices were lack of communication between farmers and users, lack of linkage between sellers and buyers, and lack of postharvest management, storage facilities, regulated and cooperative markets, transportation, and knowledge of market news. The escalating value of spices is superficially envisioned, extending from smallholder production to partial handling, which seems to be the everyday value chain.